Effects of curing conditions on the short time co-cure of CFRP–steel hybrid laminates. (May 2015) - Wang, WX; Matsubara, T; Takao, Y; Yasuda, K; Hayashi, R
In this paper, short time co-cure of CFRP–steel hybrid laminates using hot pressing and the effects of curing conditions on the interlaminar shear strength (ILSS) of the hybrid laminates are investigated experimentally to explore a cost-effective co-cure process of CFRP–steel hybrid laminates for automotive applications. A new kind of CFRP prepreg which can be cured in several minutes is used. Various curing conditions including those with and without surface treatment of metal layer, those with and without an adhesive film, three kinds of adhesive films, and three curing pressures are investigated. Short beam three-point bending tests for the hybrid laminates are conducted to evaluate the ILSS of the hybrid laminates. A cost-effective co-cure process is proposed based on the experimental results.